Measurement of serum potassium levels in patients with acute myocardial infarction - M Vinod Kumar; D Narayana Murthy (Asian Journal of Medical Research, 2019)
Background: To assess serum potassium levels in patients with acute myocardial infarction. Methodology: Sixty- four adult patients with AMI of either gender was enrolled. Patients of AMI were put in group I and healthy control in group II. 5 ml venous blood samples were collected from anti- cubital vein under aseptic precautions on the day of admission within 12 hours. All the samples were sent for analysis in laboratory for the estimation of potassium level. Results: Age group <40 years had 17 males and 12 females in group I and 18 males and 10 females in group II and >40 years had 20 males and 15 females in group I and 22 males and 14 females in group II. The mean serum potassium level in group I was 3.40 mEq/L and in group II was 4.90 mEq/L. The difference was significant (P< 0.05). Conclusion: Changes in potassium levels might act as a predictor for assessing the prognosis. Patients with AMI had lower serum potassium level as compared to healthy control.